Women's empowerment in agriculture: What role for food security in Bangladesh? - Sraboni, Esha; Quisumbing, Agnes R.; Ahmed, Akhter (University Press Limited, 2021)
While Bangladesh has experienced steady advances in food production through the adoption of agricultural technologies, chronic food insecurity remains a challenge. Similar to other countries in South Asia, there is a strong gender dimension to food insecurity and malnutrition in Bangladesh. In South Asia, the low status of women and gender gaps in health and education contribute to chronic child malnutrition (Smith et al. 2003) and food insecurity (von Grebmer et al. 2009), even as other determinants of food security, such as per capita incomes, have improved. Renewed interest in agriculture as an engine of inclusive growth and specifically in women’s empowerment has highlighted the need to develop indicators for measuring women’s empowerment, to examine its relationship to various food security outcomes, and to monitor the impact of interventions to empower women.